Teknologi Solidifikasi/Stabilisasi Secara Termal Menggunakam Tanah Liat (Clay) Dan Fly Ash - Irma Kurnia Fitri; Jon Efendi (Jurnal Periodic Jurusan Kimia UNP, 2021)
Industrial wastes generated from various industrialization activities usually contain a variety of toxic heavy metals. The resulting heavy metal is very toxic and is detrimental to the health of living things. Various technologies have been developed to deal with heavy metal waste. One of them is the method of remediation of solidification / stabilization. In this review, what will be discussed is the method of thermal solidification / stabilization. Thermal technology in the method of solidification / stabilization is a very useful method with low cost and simple methods. Stabilized metal waste can be obtained as building materials such as bricks. Vitrification or thermal methods are thermal waste treatments that convert waste into glass or crystalline materials. Most of these methods operate at 1200 ° C. In the study (I.B. Singh, 2006) solidification / thermal stabilization using fly ash binder and clay. In his research using thermal combustion temperatures of 850 ° C, 900 ° C and 950 ° C. Thermal treatment with fly ash and clay binder can reduce contaminants to the maximum.